Relevansi Benedictine Hospitality Bagi Praktik Hospitality Gereja Metaverse - Winardi, Daniel (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
This article explores how metaverse worship can become essential for churches to accommodate worship activities amid the Covid-19 pandemic situation and beyond. The advancement of metaverse technology enables its users to be present in the virtual world using their own avatars using integrated with various contexts of life, such as school, shopping, entertainment, and religion. Metaverse itself has developed since 2016 and has been used for multiple church activities. With such rapid development, the church should be able to think critically about the many theological aspects of a metaverse service, especially the practice of hospitality in such a service. I argue that churches can learn from the Benedictine tradition to strengthen and complement things that are missing from their practice of hospitality. Amid the pros and cons of hospitality in a metaverse service, I believe that while an ideal method of hospitality cannot be implemented in a metaverse service yet, Christians should nevertheless allow churches that have or have not held a metaverse service to continue to seek for their own pattern of hospitality as time goes on.